Effect of Hydrogen Peroxide on Passive Film Behavior of 304L stainless Steel - Mraied, Hesham; Sharfeddin, Asma (AlQalam Journal of Medical and Applied Sciences, 2025)
Different grades of austenitic stainless steels such as 304L, 316L, and nickel free high nitrogen austenitic stainless steels are used in biomedical applications due to their biocompatibility, adequate mechanical properties and excellent corrosion resistance. The performance of these alloys can be altered due to the presence of reactive species like hydrogen peroxide, a bi-product of the inflammatory response in the human body. In this study the corrosion behavior of 304L stainless steel was investigated in normal saline solution dopped with 8 ml/L hydrogen peroxide to simulate inflammation. Cyclic polarization, electrochemical impedance spectroscopy and Mott-Schottky analysis were used to study the corrosion resistance, passive film stability and semi conducting properties of the alloy. It was found that the addition of hydrogen peroxide increased the corrosion rate and defect density of the passive film and allowed for the growth of a thicker still unstable oxide layers. These findings revealed the important role of oxidative environments (inflammatory conditions) on the corrosion behaviour of 304L stainless steel. Thus, the significance of advanced alloy design, surface modifications, and protective measures to enhance corrosion resistance under such conditions.